ANALISIS SEBARAN BUTIR KEGIATAN PUSTAKAWAN BERDASARKAN PERMENPAN-RB NOMOR 9 TAHUN 2014 - Qorni Novianto, Achmad (BACA: Jurnal Dokumentasi dan Informasi, 2019)
The success of librarians in developing their careers depend on their success in carrying out various items of librarian activities in Permenpan-RB No.9, 2014. Librarian activities in Permenpan-RB No.9, 2014 were added with some items which had not been covered by the previous rules. This study aims to determine the distribution of librarian activities based on Permenpan-RB No.9, 2014 and how its implemented in the Library of Malang State University. This research used a descriptive method. Data collection is done by research document and interview some informans. The results of the study showed that: (1) the Malang State University Library has not been able to carry out all the activities in Permenpan-RB No.9, 2014; (2) the largest portion of the implementation of the main task of the librarian is still dominated by items of activity according to the level of hierarchy (38%-63%), under the level of position (28%-47%), and above the position level (0-18%); and (3) there are several librarians who carry out two levels of activities under their position, even outside of their position groups.